Implementasi Sistem Aplikasi Pembayaran Sekolah dan Pendaftaran Siswa Berbasis Web - Sachrul Sidiq; Fa`asya Vladimar Kasidin; Shafly Fawwaz Fadhlullah; Wasis Haryono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Raudhatul Athfal Nurul Hidayah is a kindergarten located in Rawa Panjang, Bojong Gede, Kabupaten Bogor, Jawa Barat. The use of technology in education is increasing, especially in terms of school administration such as tuition payments and new student registration. The online tuition payment and registration system is designed to facilitate the administration process for schools and parents of students. With this system, parents can make tuition payments and student registration online through an application or website, without having to come directly to the school. This study aims to develop and implement an efficient and user-friendly online tuition payment and registration system.The methods used include system design, collecting user needs data, and system testing. The results of the study show that this system can reduce the time and costs required in the payment and registration process, as well as increase data transparency and accuracy. This system also makes it easier for schools to manage financial data and student registration. Thus, the online tuition payment and registration system can be a practical solution in supporting the digitalization of school administration